2014
DOI: 10.2134/agronj14.0088
|View full text |Cite
|
Sign up to set email alerts
|

Digital Image Analysis and Spectral Reflectance to Determine Turfgrass Quality

Abstract: ABSTRACTe limitations of the conventional visual rating system used to assess turfgrass quality include its subjective nature and the need for properly trained observers who can discern di erences among treatments or turfgrass varieties. e objective of our study was to investigate if digital image analysis (DIA) and spectral re ectance [normalized di erence vegetative index (NDVI)] can be used to evaluate turfgrass varieties. Trials were established at New Mexico State University and visual quality ratings, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 22 publications
5
37
0
3
Order By: Relevance
“…Moreover, our visual quality data mirrored percentage green cover and NDVI measurements and our correlation analysis indicated a strong association between quality and NDVI and cover. These findings support those of Schiavon et al (2014) and Leinauer et al (2014) who also reported a significant correlation between subjective quality ratings taken on an ordinal scale and objective NDVI and DIA measurements.…”
Section: Soil Hydrophobicitysupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, our visual quality data mirrored percentage green cover and NDVI measurements and our correlation analysis indicated a strong association between quality and NDVI and cover. These findings support those of Schiavon et al (2014) and Leinauer et al (2014) who also reported a significant correlation between subjective quality ratings taken on an ordinal scale and objective NDVI and DIA measurements.…”
Section: Soil Hydrophobicitysupporting
confidence: 89%
“…Normalized difference vegetation indices (NDVI) were determined with a GreenSeeker Hand Held Optical Sensor Unit Model 505 (Trimble Corp., Sunnyville, CA) attached to a shoulder strap and held approximately 80 cm above the canopy. The unit was operated at walking speed (approximately 4 km h -1 ), thereby scanning a 100 cm wide area perpendicular to the direction of walking (Bell et al, 2009;Leinauer et al, 2014). Turfgrass quality was assessed visually on a 1 to 9 scale (1 = dead turf and 9 = dark green, uniform turf).…”
Section: Methodsmentioning
confidence: 99%
“…Reflectanceā€based methods are more objective than traditional visual ratings, and the two methods are well correlated (Trenholm et al, 1999; Bell et al, 2009; Bremer et al, 2011a; Schiavon et al, 2011; Rimi et al, 2013; Leinauer et al, 2014). Still, several studies have demonstrated the limitations of replacing visual ratings with reflectanceā€based methods.…”
mentioning
confidence: 99%
“…Spectral reflectance has been widely used by many researchers for evaluating drought response of various turfgrass species (Fenstermakerā€Shaulis et al, 1997; Jiang and Carrow, 2007; Jiang et al, 2009; Merewitz et al, 2010; Rowland et al, 2014). Trenholm et al (1999) and Leinauer et al (2014) reported that NDVI was highly correlated with visual turf quality and shoot density of seashore paspalum.…”
Section: Methodsmentioning
confidence: 99%